PENGARUH GOOD CORPORATE GOVERNANCE (GCG), PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ramadhan, Tiara; Afrah Junita; Tuti Meutia (Jurnal Mahasiswa Akuntansi Samudra, 2025)
This study aims to analyze the effect of Good Corporate Governance (GCG), profitability, and company size on company value in banking companies listed on the Indonesia Stock Exchange. This type of research is quantitative using secondary data in the form of annual financial reports of companies selected through purposive sampling method. Data analysis was performed using SPSS software version 22 with a multiple linear regression approach. The results of the study indicate that Good Corporate Governance (GCG) has a negative and significant effect on company value. Profitability has a positive and significant effect on company value, while company size has a positive but insignificant effect on company value. This finding implies that ineffective GCG implementation can reduce company value, while increased profitability contributes significantly to increasing company value. In addition, company size is not a dominant factor influencing company value.